2021
DOI: 10.1038/s41598-021-88413-2
|View full text |Cite
|
Sign up to set email alerts
|

High immune efficacy against different avian influenza H5N1 viruses due to oral administration of a Saccharomyces cerevisiae-based vaccine in chickens

Abstract: A safe and effective vaccine is the best way to control large-scale highly pathogenic avian influenza virus (HPAI) A (H5N1) outbreaks. Saccharomyces cerevisiae (S. cerevisiae) is an ideal mucosal delivery vector for vaccine development, and we have previously shown that conventional administration of a S. cerevisiae-based vaccine (EBY100/pYD1-HA) via injection led to protection against the homologous H5N1 virus in a mouse model. Because the diameter of S. cerevisiae is approximately 10 μm, which results in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…After duplicate removal, 77 publications were screened, and 54 underwent full-text assessment. Ultimately, our dataset included data from 46 trials across 20 experimental studies [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], as detailed in Appendix Table 2. These trials collectively involved 863 SPF chickens.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removal, 77 publications were screened, and 54 underwent full-text assessment. Ultimately, our dataset included data from 46 trials across 20 experimental studies [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], as detailed in Appendix Table 2. These trials collectively involved 863 SPF chickens.…”
Section: Resultsmentioning
confidence: 99%
“…S. cerevisiae has been one of the most popular heterologous expression hosts in biotechnology, and it is increasingly employed in oral vaccine development [ 10 16 , 37 41 ]. Our previous study [ 13 ] showed that the expression of LTB fused with a synthetic Dengue tetravalent antigen using S. cerevisiae was potentially useful as an oral vaccine against Dengue viruses.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of them were also able to protect vaccinated animals against direct challenge from their target pathogen. These include candidate yeast oral vaccines against red-spotted grouper nervous necrosis virus in convict groupers ( Cho et al, 2017 ); Helicobacter pylori in mice ( Cen et al, 2021 ); cyprinid herpesvirus-3 in the common carp ( Ma et al, 2020 ); avian H5N1 influenza virus in chickens ( Lei et al, 2021b ); and white spot syndrome virus in shrimp ( Ananphongmanee et al, 2021 ), and among others. This growing list of successful animal vaccines suggests that cell-surface display is an effective technology for creating effective yeast oral vaccines.…”
Section: Emerging Yeast Oral Vaccines For Infectious Diseasesmentioning
confidence: 99%